Pregnancy as a valuable period for preventing hypoxia‐ischemia brain damage. Issue 70 (18th June 2018) - Netto, C.A.; Sanches, E.F.; Odorcyk, F.; Duran‐Carabali, L.E.; Sizonenko, S.V.
Abstract: Neonatal brain Hypoxia–Ischemia (HI) is one of the major causes of infant mortality and lifelong neurological disabilities. The knowledge about the physiopathological mechanisms involved in HI lesion have increased in recent years, however these findings have not been translated into clinical practice. Current therapeutic approaches remain limited; hypothermia, used only in term or near‐term infants, is the golden standard. Epidemiological evidence shows a link between adverse prenatal conditions and increased risk for diseases, health problems, and psychological outcomes later in life, what makes pregnancy a relevant period for preventing future brain injury. Here, we review experimental literature regarding preventive interventions used during pregnancy, i.e., previous to the HI injury, encompassing pharmacological, nutritional and/or behavioral strategies. Literature review used PubMed database. A total of forty one studies reported protective properties of maternal treatments preventing perinatal hypoxia‐ischemia injury in rodents. Pharmacological agents and dietary supplementation showed mainly anti‐excitotoxicity, anti‐oxidant or anti‐apoptotic properties. Interestingly, maternal preconditioning, physical exercise and environmental enrichment seem to engage the same referred mechanisms in order to protect neonatal brain against injury. This construct must be challenged by further studies to clearly define the main mechanisms responsible for neuroprotection to be explored in experimental context, as well as to test their potential in clinical settings.